The needs for understanding the fundamentals of Islamic tourism city from the Shariah perspective - Ruzulan, Zulaipa; Jamaludin, Mohammad Aizat; Aris Anuar, Ahmad Nazrin; Musa Fathullah Harun, Hanifah (UTM Press, 2022)
Strategic planning and management of the Islamic tourism activities in the city are significant owing to the adherence to any available regulations enforced by the city's local authority. Since the recognition of the Islamic tourism industry has grown considerably in recent years as part of a new niche segment of the tourism industry; thus, the concept of the Islamic tourism city is still new and vague. This paper purposely aims to explore the need for understanding the fundamentals of the Islamic tourism city and its features to differentiate it from the conventional tourism city. This study employs a qualitative research methodology in which the in-text document method was used for the data collection, and the data was subsequently analysed using content analysis until the study's objective was met. The study has found that the available discussions on the concept of the Islamic tourism city are exhausted, and this could influence the governing process of Islamic tourism city whether it is in line with the Islamic teaching since the previous study less explores the concept. It is suggested that related parties such as the Islamic tourism planner, the local authorities and the academicians actively establish the concept of an Islamic tourism city because it is a necessity today due to the availability of the Islamic tourism products in the cities. Likewise, mismanagement could happen if there is no proper management of the Islamic tourism city within the Shariah principles.